Facilitating gene editing in potato: a Single-Nucleotide Polymorphism (SNP) map of the Solanum tuberosum L. cv. Desiree genome - Sevestre, François (Sci Rep, 2020)
Genome editing is a powerful tool for plant functional genomics allowing for multiallelic targeted mutagenesis. The recent development of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR associated protein 9 (Cas9) systems for gene editing in plants allows for simple, cost-effective introduction of site-specific double-stranded DNA breaks. The nuclear genomes of a homozygous doubled-monoploid potato clone (DM) and a heterozygous diploid clone (RH) have been sequenced in 2011. However, common potato cultivars display a highly heterozygous autotetraploid genome thus complicating target design for tetra-allelic gene editing. Here, we report on the SNP physical map of the widely used Solanum tuberosum L. cv. Desiree and on the position of the diverse indels providing an essential tool for target design in genome editing approaches. We used this tool for designing a specific gRNA and successfully knocking-out a newly discovered starch synthase gene (SS6) in potato. Resequencing data are publicly available at the Sequence Read Archive of the NCBI (accession number: PRJNA507597) and will represent a valuable resource for functional genomic studies of various metabolic pathways, cell and plant physiology as well as high-throughput reverse genetics in potato.